SIROSIS HEPATIS DEKOMPENSATA PADA ANAK - Rima Yuliati Muin; Julius Roma; Mutmainnah Mutmainnah; Ibrahim Abd Samad (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Cirrhosis hepatic is a diffuse chronic liver disease characterized by fibrosis and nodules formation. The reporter presented a case of an 8 years girl who was referred from RSU Bone with Nephritic Syndrome. Through anamnesis, physical examination, laboratory and USG exam, the girl finally was diagnosed as Cirrhosis Hepatic. Based on the clinical symptoms prolonged icteric, ascites, encephalopathy and neurological disorders and the laboratory tests: increased billirubin level (>1.5 mg%), decreased albumin level (<2.5 gr%), the prognosis was poor